Implementing Official Dollarization - Lonnberg, Ake (IMF Working Papers; Working Paper ;, 2010)
This paper identifies key aspects that countries willing to officially dollarize must necessarily address. Based on country experiences, it discusses the critical institutional bases that are necessary to unilaterally introduce a new legal tender, describes the relevant operational issues to smooth the transition toward the use of the new currency, and identifies key structural reforms that are necessary to favor the sustainability over time of this monetary regime. The paper is aimed at providing preliminary guidance to policy makers and practitioners adopting official dollarization. The paper does not take a position on how appropriate this monetary arrangement is. Experiences from adopting dollarization in Ecuador, El Salvador, Kosovo, Montenegro, and Timor-Leste are illustrated briefly.